Opponents of domestic partners registry - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows people of varying ages who are opponents of the domestic partners registry at chambers of the Santa County Board of Supervisors. Sign reads, "Will San Jose's fait be like Sodom & Gommorah? Genesis, 19: 1-25 (Story of two cities), Isaiah 3:9 (Fallen Leaders), Romans 1:24-32 (Rejection of God).